ثبوت القصاص واستيفاء الحقوق للإمام عالم محمد بن حمزة الآيديني المتوفى قريباً من عام 1122 هـ.: دراسة وتحقيق - الكوزل حصاري، عالم محمد بن حمزة الآيديني، ت. 1122 هـ.; صالح، طه أحمد (ديوان الوقف السني - مركز البحوث والدراسات الإسلامية, 2024)
1. العديني هو العالم والمفسر والمحدث والمفتي عالم محمد حمزة. 2. اشتهر رحمه الله بكوزل حصاري المعروف بأمير زاده الحنفي المفتي، وكزلجي: تصغير كوزل أي جميل. 3. العيديني نسبة إلى مدينة وولاية أيدين التركية. 4. تعرض العديني لظلم تاريخي من حيث قلة المصادر التي توضح لنا سيرته ومساره العلمي والحياتي. 5. كان للإمام العيديني شهرة كبيرة في الكتابة. وكان ماهرا في كتابة الرسائل في كثير من العلوم، مثل الفقه والأصول والمذهب والتفسير وغيرها. 6. وجدت نسختين مكتوبتين بخط اليد من هذه المخطوطة، وبيانهما كما يلي: النسخة الأولى: محفوظة في مكتبة قيصرية رشيد بتركيا رقم (٣٥٢٥) تحت عنوان رسالة في إثبات القصاص واستيفاء الحقوق. 7. النسخة الثانية: نسخة موجودة في مكتبة أسعد أفندي بتركيا رقم (٤٠٠٦) تحت عنوان: إثبات القصاص واستيفاء الحقوق. 8. تميزت النسخ بخط جميل وواضح ومقروء. 9. تتميز هذه المخطوطة بجودة الخط، حيث أنها كتبت بخط النسخ الجميل. ويتميز أيضا بالتوافق شبه الكامل بينهما، وعدم السهو، وعدم وجود أخطاء إملائية. 1. Al-Idini is the scholar, interpreter, hadith scholar, and mufti: the scholar of Muhammad Hamza. 2. He was famous, may God have mercy on him, for Kozel Hisari, known as Amir Zadeh al-Hanafi al-Mufti, and Kozelji: diminutive of Kozel, meaning beautiful. 3. Al-Aydını: named after the Turkish city and state of Aydın. 4. Al-Ideni was subjected to historical injustice in terms of the lack of sources that show us his biography and his scientific and life path. 5. Imam Al-Aydini had a great reputation for writing. He was skilled in writing treatises on many sciences, such as jurisprudence, principles, doctrine, interpretation, and others. 6. I found two handwritten copies of this manuscript, which are described as follows: The first copy: preserved in the Kayseri Rashid Library, in Turkey, number (3525) under the title of a treatise on proving retribution and fulfillment of rights. 7. The second copy: A copy in the Asaad Effendi Library in Turkey, No. (4006), under the title: Proving retaliation and fulfilling rights. 8. The copies were distinguished by beautiful, clear and legible handwriting. 9. This manuscript is distinguished by the quality of the handwriting, as it was written in a beautiful Naskh script. It is also distinguished by the almost perfect correspondence between them, the lack of omissions, and the lack of spelling errors."
Keywords: القرآن الكريم -- اللغة العربية -- الأصول الفقهية -- الآيديني، عالم محمد حمزة، ت. 1122 هـ